TOXIC MASCULINITY PENGGUNAAN SKINCARE DALAM PENCIPTAAN SENI LUKIS MIX MEDIA - Alfian Nugraha, Aldi; Akbar, Budiman (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2024)
Toxic masculinity refers to gender norms that dictate men must always be strong, should not show weakness or emotions such as sadness, and must refrain from self-care practices like skincare, which some societies perceive as feminine. This research aims to demonstrate that men can also use skincare as a form of self-care. The study employs a qualitative method with an artistic research approach, combining art creation with direct research methods such as internships, exploration, and interviews with sources, allowing for a deeper understanding from a broader perspective. In this study, the researcher uses Charles Sanders Peirce's semiotic theory to analyze the creative work, as this theory explains how meaning is derived from symbols. The use of mixed-media painting in this context enables the creator to combine various materials, such as acrylic paint, mirrors, facial masks, and other media, to produce complex visual effects and textures.